„Myśl” Leonida Andrejewa w kontekście „Myśli” Blaise'a Pascala - Andruszko, Czesław (Studia Rossica Posnaniensia, 2011)
The article describes Thought by Leonid Andreyev as a kind of contemporary artistic reflection of paradoxes descended from Thoughts by Blaise Pascal. The short story Thought by Leonid Andreyev is examined as a creative orientation of its author to Thoughts by Blaise Pascal. A comparative analysis of both works proves that, beside the antynomic vision of man and the world, Andreyev shares with Pascal a similar usage of notions such as thought, imagination, and abyss. The former, however, simplifies the ideas and views of the prominent philosopher in order to better reach the consciousness of the modern reader.